2019
DOI: 10.1093/schbul/sby191
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide, Integrative Analysis Implicates Exosome-Derived MicroRNA Dysregulation in Schizophrenia

Abstract: Genetic variants conferring risk for schizophrenia (SCZ) have been extensively studied, but the role of posttranscriptional mechanisms in SCZ is not well studied. Here we performed the first genome-wide microRNA (miRNA) expression profiling in serum-derived exosome from 49 first-episode, drug-free SCZ patients and 46 controls and identified miRNAs and co-regulated modules that were perturbed in SCZ. Putative targets of these SCZ-affected miRNAs were enriched strongly for genes that have been implicated in prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 42 publications
1
71
0
Order By: Relevance
“…Dysregulation of exosome-derived miRNA expression has been reported in schizophrenia and localized breast cancer [53, 54]. These studies suggested that the expression of miRNAs in exosomes changed significantly under different conditions.…”
Section: Discussionmentioning
confidence: 96%
“…Dysregulation of exosome-derived miRNA expression has been reported in schizophrenia and localized breast cancer [53, 54]. These studies suggested that the expression of miRNAs in exosomes changed significantly under different conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The observed up-regulation of miR-206 was accompanied by the down-regulation of its target, BDNF, in the blood. Since decreased expression of BDNF has been negatively associated with cognitive functions of animals, the researchers concluded that exosomal hsa-miR-206 up-regulation may contribute to BDNF dysfunction in schizophrenia, a finding which further supports the neurotrophin hypothesis of schizophrenia [94]. The details of miRNA studies covered in this section are summarized in Table 2.…”
Section: Mirnamentioning
confidence: 69%
“…miRNAs have also been profiled in the blood of patients with schizophrenia (89), with the main aim of identifying blood biomarkers of the disease. In a recent genome-wide expression study, Du et al (90) found that several miRNAs were differentially expressed in serum exosomes of patients with first-episode, drug-free schizophrenia relative to matched control subjects. Importantly, among the differentially expressed miRNAs, 11 could be used to dissociate schizophrenia samples from control samples with 75% to 90% accuracy (90).…”
Section: Noncoding Rnasmentioning
confidence: 99%
“…In a recent genome-wide expression study, Du et al (90) found that several miRNAs were differentially expressed in serum exosomes of patients with first-episode, drug-free schizophrenia relative to matched control subjects. Importantly, among the differentially expressed miRNAs, 11 could be used to dissociate schizophrenia samples from control samples with 75% to 90% accuracy (90). Despite this remarkable precision, however, blood miRNA profiling tends to produce equivocal results in the context of schizophrenia, with biomarker candidates varying across independent studies (91)(92)(93).…”
Section: Noncoding Rnasmentioning
confidence: 99%